The Role of Grass MUTE Orthologs in GMC Progression and GC Morphogenesis - Serna, Laura (Frontiers in Plant Science, 2021)
Stomata arose about 400 million years ago when plants left their aquatic environment. The last step of stomatal development is shared by all plant groups, and it implies a symmetrical cell division from the guard mother cell (GMC) to produce two guard cells (GCs) flanking a pore. In Arabidopsis, the basic helix-loop-helix transcription factor MUTE controls this step, upregulating cell-cycle regulators of the GMC division, and immediately afterwards, repressors of theses regulators like FAMA and FLP. Recently, three grass MUTE orthologues (BdMUTE from Brachypodium distachyon, OsMUTE from rice and ZmMUTE from maize) have been identified and characterized. Mutations in these genes disrupt GMC fate, with bdmute also blocking GC morphogenesis. However, because these genes also regulate subsidiary cells recruitment, which takes place before GMC division, their functions regulating GMC division and GC morphogenesis could be an indirect consequence of that inducing the recruitment of subsidiary cells. Comprehensive data evaluation indicates that BdMUTE, and probably grass MUTE orthologues, directly controls GMC fate. Although grass MUTE proteins, whose genes are expressed in the GMC, move between cells, they regulate GMC fate from the cells where they are transcribed. Grass MUTE genes also regulate GC morphogenesis. Specifically, OsMUTE controls GC shape by inducing OsFAMA expression. In addition, while SCs are not required for GMC fate progression, they are for GC maturation.